Magnetic Metal Organic Framework Immobilized Laccase for Wastewater Decolorization - Abdelfattah Amari (Processes, 2021)
The laccase enzyme was successfully immobilized over a magnetic amino-functionalized metal–organic framework Fe3O4-NH2@MIL-101(Cr). Different techniques were used for the characterization of the synthesized materials. The Fe3O4-NH2@MIL-101(Cr) laccase showed excellent resistance to high temperatures and low pH levels with a high immobilization capacity and large activity recovery, due to the combination of covalent binding and adsorption advantages. The long-term storage of immobilized laccase for 28 days indicated a retention of 88% of its initial activity, due to the high stability of the immobilized system. Furthermore, a residual activity of 49% was observed at 85 °C. The immobilized laccase was effectively used for the biodegradation of Reactive Black 5 (RB) and Alizarin Red S (AR) dyes in water. The factors affecting the RB and AR degradation using the immobilized laccase (dye concentration, temperature and pH) were investigated to determine the optimum treatment conditions. The optimum conditions for dye removal were a 5 mg/L dye concentration, temperature of 25 °C, and a pH of 4. At the optimum conditions, the biodegradation and sorption-synergistic mechanism of the Fe3O4-NH2@MIL-101(Cr) laccase system caused the total removal of AR and 81% of the RB. Interestingly, the reusability study of this immobilized enzyme up to five cycles indicated the ability to reuse it several times for water treatment.